An analysis of promotional lifestyles in family-centered consumer advertising - mahboobeh Alimohammadi (Religion & Communication, 2023)
An analysis of promotional lifestyles in family-centered consumer advertising Consumption preference" at the end of modernity, transformed human societies and individual life. The multiplicity of goods changed the content of life by changing its way of life and accelerated the attainment of the "postmodern" period. The diversity of lifestyles is born of such an atmosphere. This space was developed with the help of the media, especially television, which was the link between production and the customer, and by orienting the behaviors of the audience. From this point of view, the present article tries to examine the commercial advertisements of irib Identify the lifestyles and families in them. Examination of these messages using Fisk's semiotic model showed that social codes represent the "rich family" the most. Technical codes also consider "consumption of goods" as a factor of family cohesion and manage the interpersonal relations in families in favor of capitalist ideology by "commodification". The multiplicity of goods changed the content of life by changing its way of life and accelerated the attainment of the "postmodern" period. The diversity of lifestyles is born of such an atmosphere. This space was developed with the help of the media, especially television, which was the link between production and the customer, and by orienting the behaviors of the audience. From this point of view, the present article tries to examine the commercial advertisements of irib Identify the lifestyles and families in them.